2012
DOI: 10.4172/2157-2518.s4-003
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Sun-Protective Behaviour at an Outdoor Spectator Sporting Event in a Region of High Sun Exposure

Abstract: Introduction: Few studies have described observed sun-protection behaviours. We aimed to describe the prevalence of observed sun-protection behaviour of a high-risk population in tropical Queensland engaged in outdoor leisure activity, to act as a baseline for future comparisons and to highlight the need for further work to improve sun-protective behaviours in this high risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Similar low adherence to sun protective recommendations has been reported in previous Australian studies (Dobbinson et al, ; Nikles & Harrison, ; Volkov, Dobbinson, Wakefield, & Slevin, ). Dobbinson et al's () longitudinal study in one jurisdiction reported significant increases in rates of hat wearing over time, but rates of hat wearing in the most recent survey remained relatively low, with only 39% reporting wearing any type of hat while outdoors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar low adherence to sun protective recommendations has been reported in previous Australian studies (Dobbinson et al, ; Nikles & Harrison, ; Volkov, Dobbinson, Wakefield, & Slevin, ). Dobbinson et al's () longitudinal study in one jurisdiction reported significant increases in rates of hat wearing over time, but rates of hat wearing in the most recent survey remained relatively low, with only 39% reporting wearing any type of hat while outdoors.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of rates of wearing sun protective clothing (three‐quarter or long sleeves), the current study results (14%) are similar to Nikles and Harrison's () results of 10%, but lower than both Dobbinson et al's () and Volkov et al's () most recent survey results (27% and 19%, respectively). Although the risk of sun exposure and resulting skin damage is documented and well known, the present study indicates that the study population is continuing to overexpose themselves to UVR.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…type of swimwear). There have been a few studies to date that used a mix of surveys and on-site evaluations of SunSmart programs in Hawaii (Glanz et al, [18]) and observations of public recreation venues (Dobbinson et al, [19], Nikles & Harrision, [20]). Very few however record sun-safe behaviours of children in school settings..…”
Section: Methodsmentioning
confidence: 99%
“…Poor levels of personal sun protection are commonly observed in study populations , where improved sun protection behavior is higher among older adults and females ; however, these findings sharply contrast with those reported for an outdoor event in skin cancer‐prone tropical Queensland. Nikles and Harrison found that significantly more children (45.1%) than adults (27.1%) wore wide‐brimmed, legionnaires or bucket hats, and sun‐protective behaviors were generally better for males than females.…”
Section: Introductionmentioning
confidence: 99%